Alcmaeonids and Their Role in the Battle of Marathon - Hansen, Jason (My University, 2011)
This research addresses the question of whether or not the Alcmaeonidae (a leading family in ancient Athens) signaled the Persians in their attempted invasion of the city of Athens, following the Battle of Marathon in 490 BCE.
Color poster with text and images.
Keywords: Alcmeonid family; Marathon, Battle of, Greece, 490 B.C.; Posters